Censo 2022 : ¿quiénes somos? - D'Agostino, Lucrecia; Romero Marchesini, Natalia (2022)
El Censo 2022 pretende marcar un nuevo camino en la tradición argentina a partir de un giro subjetivo en el modo de concebir y registrar a la población. Por primera vez la pregunta por la identidad de género se enmarca dentro de la propuesta de reconocimiento de identidades heterogéneas frente a definiciones binarias impuestas desde el Estado. El interrogante principal ya no es "¿cuántos somos?", sino "¿quiénes somos?"
The 2022 Census aims to mark a new path in the Argentine tradition based on a subjective shift in the way of conceiving and registering the population. For the first time, the question of gender identity is framed within the proposal to recognise heterogeneous identities in the face of binary definitions imposed by the state. The main question is no longer "how many of us are we", but rather "who are we?
Keywords: Censo 2022; Giro subjetivo; Binarismo estadístico; Census 2022; Subjective turn; Statistical binarism